Sistotremastrum limonadense sp. nov. from French Guiana - Gruhn, Gérald; Alvarado, Pablo (Phytotaxa, 2021)
A new species of Sistotremastrum J. Erikss. (Basidiomycota, Trechisporales) with (6-8)-spored basidia is described and supported by morphology and phylogenetic analyses based on ITS rDNA sequences.